PENGARUH BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN PEMEDIASI KOMITMEN AFEKTIF DI SEKRETARIAT KABUPATEN BADUNG - Ariani, Ayu Putu; Sintaasih, Desak Ketut; Putra, Made Surya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study was to determine the significance of the influence of organizational culture on affective commitment, the influence of affective commitment on OCB, the influence of organizational culture on OCB and the mediating effect of affective commitment on the influence of organizational culture on OCB. These samples included 83 employees are determined using proportionate random sampling method. Data were obtained from questionnaires and interviews. The analytical tool used in this study using Partial Least Square (PLS). The results showed that organizational culture positive effect on affective commitment, the better the culture of the organization, affective commitment is also getting stronger. Affective commitment positively affects the OCB, the stronger the affective commitment has embraced the OCB behaviors also higher. Organizational culture positive influence on OCB, semaik both an organizational culture that is applied then OCB also higher. Results of testing the hypothesis is further produced that affective commitment partially mediates the influence of organizational culture on OCB.
Keywords: organizational culture, affective commitment and OCB